Clinical Usefulness of the Serum Carboxypeptidase B Activation Peptide in Acute Pancreatitis - Pezzilli, Raffaele; Morselli-Labate, Antonio Maria; Barbieri, Anna Rita; Platè, Livia (JOP. Journal of the Pancreas, 2016)
Objective To assess the sensitivity and specificity of the serum carboxypeptidase B activation peptide in diagnosing and determining the severity of acute pancreatitis. Patients Twenty consecutive patients with acute pancreatitis were studied on admission to the Emergency Room: 11 patients had mild pancreatitis, and 9 patients, severe pancreatitis. Twenty consecutive patients with non-pancreatic acute abdomen and 20 healthy subjects were also studied. Main outcome measures Serum carboxypeptidase B activation peptide was determined using radioimmunoassay. Results Nineteen of the 20 patients with acute pancreatitis (95.0%) had serum carboxypeptidase B activation peptide concentrations above the upper reference limit, whereas 1 of the 20 patients with non-pancreatic acute abdomen (5.0%) and none of the healthy subjects had serum levels of this protein above the upper reference limit. The serum carboxypeptidase B activation peptide concentrations of patients with severe acute pancreatitis were significantly higher than those of patients with mild acute pancreatitis on the 2nd (P=0.044) and 3rd days (P=0.028) of the study. The overall sensitivity and specificity of carboxypeptidase B activation peptide in assessing the severity of acute pancreatitis were 84.6% and 59.4%, respectively. Conclusions Serum carboxypeptidase B activation peptide may be used simultaneously both to diagnosis and assess the severity of acute pancreatitis on admission to the Emergency Room. Image: Box and whisker plots of serum CAPAP, amylase, lipase and C-reactive protein.